Analisis Hubungan Risiko dan Imbal Hasil Portofolio Saham di Pasar Modal Indonesia: Perspektif Diversifikasi dan CAPM - Mukhtaruddin; Rizqi Firdaus; M Alan Saputra; Kemas Muhammad Arkan Albukhori (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the relationship between risk and return in stock portfolio management in the Indonesian capital market using diversification and the Capital Asset Pricing Model (CAPM). The sample consists of 30 liquid stocks listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The analysis includes annual return calculations, volatility estimation, beta measurement, and Sharpe Ratio evaluation to assess portfolio performance relative to risk. The findings indicate that portfolio diversification significantly reduces unsystematic risk, while systematic risk remains the main determinant of portfolio return. The application of CAPM provides insight into stock sensitivity to market movements, enabling investors to align investment decisions with risk preferences and target returns. These findings also support the weak-form efficient market hypothesis. This research offers practical insights for investors seeking to optimize returns while managing risk more effectively in the Indonesian capital market.